2018
DOI: 10.1186/s13756-018-0362-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbapenem non-susceptibility of Klebsiella pneumoniae isolates in hospitals from 2011 to 2016, data from the German Antimicrobial Resistance Surveillance (ARS)

Abstract: BackgroundCarbapenem resistance in Klebsiella pneumoniae is of significant public health concern and recently spread across several countries. We investigated the extent of carbapenem non-susceptibility in K. pneumoniae isolates in Germany.MethodsWe analysed 2011–2016 data from the German Antimicrobial Resistance Surveillance (ARS) System, which contains routine data of antimicrobial susceptibility testing from voluntarily participating German laboratories. Klebsiella pneumoniae isolates tested resistant or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 25 publications
6
24
0
1
Order By: Relevance
“…Increasing resistance to antibiotics is one of the main problems within present medicine. The rapid spread of CPE, including those with MBLs, has become a critical challenge of infection control and treatment [8]. The first carbapenemaseproducing bacteria were identified in 1991 in Japan [9].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing resistance to antibiotics is one of the main problems within present medicine. The rapid spread of CPE, including those with MBLs, has become a critical challenge of infection control and treatment [8]. The first carbapenemaseproducing bacteria were identified in 1991 in Japan [9].…”
Section: Discussionmentioning
confidence: 99%
“…Uwe Koppe et al [20] reported the number of KP isolates tested non-susceptible to 3 carbapenems (imipenem, meropenem, and ertapenem). In our study, we explored the changing trends of KP isolates resistance to 1, 2, and 3 carbapenems.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring data from the German Antimicrobial Resistance Surveillance (ARS) show that the isolation rate of K. pneumoniae, which was not sensitive to carbapenems, in Germany in 2011-2016 was only 0.63%. [17] In addition, K. pneumoniae, which was not sensitive to carbapenems, was often resistant to other antibiotics, such as gentamicin, Sulfanilamide and tegacyclin.…”
Section: Discussionmentioning
confidence: 99%